Alternative Forms and Approaches to Operatic Practice in Australia (PlaySpace, 2023)
This timely research presents an excerpt of my analysis of opera and operatic practice in Australia in 2021. The aim of the broader research is to interrogate the sustainability, viability and evolution of the Australian operatic field. Situated during the globally recognised Coronavirus pandemic era, this qualitative research project was conducted over the period 2018–2021. The fieldwork component of the research is an investigation conducted through long-form interviews with a selection of the central figures in the operatic field in Australia today. This excerpt is from Chapter 8, Part III Stories We Tell: Making and Staging Opera in Australia. I examine how and why repertoire opera is being reframed, and who is taking the lead in this reframing, juxtaposed with the personal and societal cost of performing unexamined extant opera works and perpetuating the ‘opera gaze’. The vision and division of the operatic field is deconstructed in an exploration of contemporary Australian opera and contemporary practices, fictional ritual spaces, and explorations of gender, Aboriginal opera and decolonising the postcolonial operatic lens.